Board of directors, information asymmetry, and intellectual capital disclosure among banks in Gulf Co-Operation Council - Zuaini Ishak; Al-Ebel, Abood Mohammad (Penerbit Universiti Kebangsaan Malaysia, 2013)
The main thrust of this paper is to examine the intellectual capital (IC) disclosure of 137 listed banks in Gulf Co-operation Council (GCC) nations using a content analysis approach. Instead of examining the effect of board characteristics in isolation from each other, this study extends previous research on the determinants of IC disclosure by considering board effectiveness score in relation to IC disclosure. Moreover, this study extends previous studies in board-IC disclosure relationship by investigating the hypothesized impact of information asymmetry in moderating this relationship. Our findings show that IC disclosure is positively associated with the effectiveness of board of directors. In addition, our study provides evidence that the level of information asymmetry in GCC bank moderates the relationship between board effectiveness and IC disclosure. The finding is important for policymakers as it confirms that the effectiveness of board of directors in protecting the investors depends on the level of information asymmetry.